Job Security and Risk‐Taking: Theory and Evidence From Professional Football. (10th December 2018) - Slade, Peter; Tolhurst, Tor
Abstract : This article investigates how job security impacts risky decision making. In a theoretical model, we show how risk‐taking can be affected by job security. Agents with moderate job security become more risk averse as their job security increases. Conversely, agents with very high (or low) job security act in a more risk neutral manner. We test these predictions using data on head coaching decisions from the National Football League, finding that job security has a negative and statistically significant effect on risk‐taking.